Association between air pollutants with FeNO among primary school children at petrochemical industries - Yusoff, Ahmad Fahmi; Jalaludin, Juliana; Suhaimi, Nur Faseeha (Research India Publications, 2016)
Children's increased risk of respiratory diseases is possibly due to air pollutants exposure. This study aims to determine the association between air pollutants and respiratory inflammation among school children at petrochemical industries in Kemaman, Terengganu. A cross-sectional comparative study was conducted among selected healthy school children from primary schools in Kemaman. Questionnaires were used to determine reported respiratory symptoms. Indoor exposure to PM2.5 in classrooms was measured using DustTrak DRX Aerosol Monitor; VOCs using PbbRAE, while NO2 and SO2 using LaMotte Air Sampler. Fractional exhaled Nitric Oxide (FeNO) was measured by instructing respondents to exhale directly into the NIOX MINO device. The median and interquartile range of concentration of PM2.5, VOCs, NO2 and SO2 in classrooms and homes of studied group was higher than the values in comparative group at p<0.001. FeNO shows a significant difference between studied and comparative group at p<0.001. NO2 and SO2 were found to be significantly associated with FeNO at p<0.05. Exposure to NO2 and SO2 is associated with FeNO in petrochemical industries area suggesting that greater exposure may influence children’s respiratory health.